Clinical experience with multigene carrier panels in the reproductive setting. (17th May 2018) - Terhaar, Catherine; Teed, Nicole; Allen, Rachel; Dohany, Lindsay; Settler, Christina; Holland, Carol; Longman, Ryan E.
Abstract: Objectives: Expanded carrier testing is acknowledged as an acceptable strategy for carrier testing by the American College of Obstetrics and Gynecology. Limited studies have investigated positivity rates of expanded carrier panels. We describe our experience with 3 commercial laboratory panels varying in size from 3 to 218 disorders. Methods: We reviewed outcomes for 3 multigene carrier screening panels: trio (3 diseases), standard (23 diseases), and global (218 diseases). All panels used targeted genotype analysis of preselected mutations via next‐generation sequencing. We calculated positivity rates for each panel. Results: Positivity rates were 7.2% for Preparent Trio, 13.2% for Preparent Standard, and 35.8% for Preparent Global. The most frequent positive results in the global panel were (in descending order): abnormal hemoglobin electrophoresis, familial Mediterranean fever, cystic fibrosis, fragile X, glucose‐6‐phosphate dehydrogenase deficiency, alpha‐thalassemia, and nonsyndromic hearing loss. Conclusions: While genetic diseases are individually rare, they are cumulatively common. Our experience illustrates that, with a panel of 218 diseases, the likelihood of identifying a carrier can be as high as 36%. Understanding panel positivity rates is one important factor for providers when choosing the right test for their practice, setting appropriate expectations for patients, and planning for follow‐up counseling. Abstract : What's already known about this topic? Expanded carrier testing is available as an assessment option. Pan‐ethnic–based testing does not rely on ethnicity as a qualification for assessing the presence of specific genetic conditions. What does this study add? This is a report of positivity frequencies for 3 multigene carrier panels offered by a single laboratory ranging from 7.2% to 35.8%. The study includes a list of the most commonly positive conditions on a large expanded carrier panel.